Web and Wireless Geographical Information Systems 13th International Symposium, W2GIS 2014, Seoul, South Korea, April 4-5, 2013, Proceedings - Pfoser, Dieter; Li, Ki-Joune (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed conference proceedings of the 13th International Symposium, W2GIS 2014, held in Seoul, South Korea, in May 2014. The 12 revised full papers presented were carefully selected from numerous submissions. The program covers a wide range of topics including Communication and Parallel Processing for Geospatial Data, Geo-Social Net, Crowdsourcing, and Trajectory, Geo-Sensor Network, Applications of W2GIS, Indoor GIS.